KEBUTUHAN PENDAMPINGAN PASTORAL UNTUK MENGATASI KECANDUAN GAME ONLINE REMAJA DI JEMAAT GMAHK PIONEER TOMPASO - Micle Edwin Tumundo; Rudolf Sagala; Stimson Hutagalung (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
The purpose of this study was to determine the importance of pastoral care for church youth who are addicted to online games. The method used is a survey with data collection techniques using a questionnaire with non-probability sampling. The number of questionnaires was collected from 66 respondents among the 130 congregations. The research subjects were the Pioneer Tompaso Seventh-day Adventist Church in Jl. Pemuda Desa Kamanga 2, Tompaso District, Minahasa Regency, North Sulawesi Province. The data were analyzed according to the five respondents' preferences for the answers to the questionnaire, ranging from strongly agree to strongly disagree. The results show that 75.8% agree and strongly agree that online games have a terrible impact on their future, and 71.4% want to get rid of online game addiction. The results also show that 62.1% of respondents need pastoral assistance and trust the pastor's guidance and advice.